Preparation and characterization of Cu-N-C electrocatalysts for oxygen reduction reaction in alkaline anion exchange membrane fuel cells - Kang, Yun Sik; Heo, Yoonhye; Kim, Pil; Yoo, Sung Jong (한국공업화학회, 2017)
In this study, Cu-N-C catalysts were prepared by annealing metal-adsorbed polyaniline (PANI) or Vulcan carbon (VC), and their electrocatalytic properties were investigated. The results showed that Cu is used for the generation of active sites as well as utilized as the active component for oxygen reduction reaction (ORR). The catalysts prepared using PANI delivered higher ORR activity than those prepared with VC. Furthermore, the ORR activities of the prepared catalysts can be tuned by the heat-treatment conditions. The PANI-derived catalyst obtained under an NH3 atmosphere showed the highest ORR performance among the prepared catalysts. (C) 2017 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.